Determinants And Moderators of Tax Planning, With Firm Size as The Control Variable - Pramudya, Wisnu Haryo; Astuti, Wuku (E-Jurnal Akuntansi; Vol 34 No 11 (2024), 2024)
This study examines the factors influencing and moderating tax planning, with firm size as a control variable. Tax planning is essential for optimizing tax liabilities, ensuring compliance, and boosting profitability. However, the factors affecting tax planning, especially in emerging markets like Indonesia, are underexplored. The research focused on contractor and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. Using Moderated Regression Analysis (MRA), the study tested several hypotheses. The findings revealed that corporate governance does not directly affect tax planning, but profitability influences tax planning and moderates the relationship between corporate governance and tax planning. Additionally, firm size does not control the impact of corporate governance on tax planning. This study contributes to the literature by highlighting the moderating role of profitability in the corporate governance-tax planning relationship, especially in the Indonesian real estate and construction sectors, and emphasizes the distinct regulatory and financial context of these industries.